Accuracy of abbreviated breast magnetic resonance imaging protocols for primary tumor and post-treatment evaluation - Lina Choridah; Kardinah Kardinah; Vincent Laiman; Zannuba Arifah Noor; Putri Noviantika Laskarsantri; Rozan Muhammad Irfan; Sariningsih Hikmawati (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Prompt and accurate detection of breast lesions is essential to improve patient outcomes, particularly in settings with limited access to extensive imaging. Abbreviated breast magnetic resonance imaging (MRI) has emerged as a potential alternative to conventional MRI, offering shorter acquisition times while maintaining high diagnostic accuracy. This study aimed to evaluate the accuracy of abbreviated breast MRI in detecting benign and malignant breast lesions, encompassing primary and post-treatment lesions. Results A total of 205 patients (277 lesions) underwent abbreviated breast MRI, which encompassed T1-weighted imaging (T1WI), T2-weighted imaging, postcontrast T1WI at 2 min, subtraction at 2 min, and turbo inversion recovery magnitude sequences on a 1.5-T MRI scanner. Of the 277 lesions, 85 were primary lesions, and 192 were post-treatment lesions. Age was significantly associated with the malignancy status. Abbreviated MRI demonstrated high diagnostic accuracy, with 92% sensitivity and 89% specificity overall, with sensitivity and specificity of 84% and 96% for primary lesions and 96% and 86% for post-treatment lesions, respectively. Compared with conventional MRI, abbreviated MRI effectively classified lesions according to breast imaging-reporting and data system categories and significantly reduced the diagnostic time. Discordant cases included premalignant lesions, a fibroadenoma, and a malignant phyllodes tumor. Conclusion Abbreviated breast MRI exhibits high sensitivity and specificity in detecting breast lesions, making it a promising alternative for primary tumor diagnosis and post-treatment evaluations. Its efficiency and shorter imaging time enhance its potential use in routine clinical practice, particularly in resource-limited settings.